2014
DOI: 10.1371/journal.pone.0090828
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs. Tablet Computer-Based Patient Education following Lung Transplantation – A Randomized Controlled Trial

Abstract: BackgroundAccurate immunosuppression is of critical importance in preventing rejection, while avoiding toxicity following lung transplantation. The mainstay immunosuppressants are calcineurin inhibitors, which require regular monitoring due to interactions with other medications and diet. Adherence to immunosuppression and patient knowledge is vital and can be improved through patient education. Education using tablet-computers was investigated.ObjectiveTo compare tablet-PC education and conventional education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 32 publications
1
79
0
Order By: Relevance
“…Studies were conducted in liver (n = 8), kidney (n = 25), heart or heart/lung (n = 2), and lung transplant recipients (n = 4), as well as mixed groups (n = 2). Of the RCTs, 11 did not report on transplant outcomes, and 10 examined them and found no effect of the intervention . Table is a detailed review of the 10 RCTs that looked at transplant outcomes (and found no intervention effect); this table also presents other outcomes that were examined in those studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in liver (n = 8), kidney (n = 25), heart or heart/lung (n = 2), and lung transplant recipients (n = 4), as well as mixed groups (n = 2). Of the RCTs, 11 did not report on transplant outcomes, and 10 examined them and found no effect of the intervention . Table is a detailed review of the 10 RCTs that looked at transplant outcomes (and found no intervention effect); this table also presents other outcomes that were examined in those studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the RCTs, 11 did not report on transplant outcomes, [45][46][47][48][49][50][51][52][53][54]57 and 10 examined them and found no effect of the intervention. 55,56,[58][59][60][61][62][63][64][65] Table 2 is a detailed review of the 10 RCTs that looked at transplant outcomes (and found no intervention effect); this table also presents other outcomes that were examined in those studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no previous studies have used tablet-based education in the context of adjuvant breast cancer therapy. A similar intervention was used to educate lung transplant recipients about adherence to immunosuppressive therapy 16 . The primary outcome in that study was treatment adherence (measured by serum drug levels), and the tablet-based education tool was found to be noninferior to conventional nurse-administered teaching, with a trend toward better adherence in patients receiving the tablet-based intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only 43% of centers met reporting thresholds for LKDs who donated in 2013, indicating that novel methods for collecting LKD follow-up data are needed. [10][11][12][13][14][15][16][17][18][19][20] However, mHealth technology has not yet been explored as a method for improving LKD follow-up, despite the well-documented challenges of collecting follow-up data. 9 Within the transplant community, mHealth technologies have been used to address numerous challenges in the field, including educating transplant recipients and candidates, improving adherence and self-management behaviors of recipients, helping patients on the waitlist find a living donor, and aiding in the screening and evaluation process of LKD candidates.…”
Section: Introductionmentioning
confidence: 99%